Cost-benefit analysis for optimum return of flood control mitigation / Nor Azliza Akbar, Amalina Amirah Abu Bakar and Siti Isma Hani Ismail - Abu Bakar, Amalina Amirah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Flood is a problem caused by precipitation and runoff particularly during periods of excessively high rainfall. Nowadays in Malaysia, flood has become a serious problem to the extent of imposing impact to the environment. This problem may cause damage to properties, loss of life, loss of utility services, loss of trading and others. However, with sophisticated technologies, some flood mitigation measures have been designed by engineers and the government allocates a lot of money for the projects. A study on flood damage assessment is necessary to identify, predict and evaluate the benefits of flood control projects. In this study, a model on flood damage assessment was developed by using Visual Basic language and the data which is used in this calculation is hypothetical data. Besides, this study is important to ensure that floods are controlled by implementing mitigation measures in order to minimize destruction to the environment. From the economic point of view, the best approach to establish the most economical flood control system was selected based on a suitable system that gives the largest benefit-cost ratio analysis or the maximum return of the net benefit. This model will be able to assist engineers in making the best decision during planning for flood control projects before the intended design can be executed.